51.9k views
3 votes
Simplify: -2x(3 - 5x)

User Chilion
by
5.0k points

2 Answers

3 votes

Answer:

10x² - 6x

Explanation:

-2x(3 - 5x)

={(-2x) . 3} - {(-2x) . 5x}

=-6x - (-10x²)

=-6x + 10x² [negative plus negative=positive]

=10x² - 6x

User Cazala
by
5.5k points
3 votes

Answer:

-6x+10x^2

Explanation:

you just have to distribute the -2x to the numbers inside the parenthesis.

hope this helps

User Redmonty
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.